Efektivitas Metode Terapi Akupunktur dan Aurikular Akupunktur pada Penurunan Nyeri Disminore Primer - Ningtyas, Listina Ade Widya; Astiti, Ni Komang Erny (ARTERI : Jurnal Ilmu Kesehatan, 2024)
Pain in cases of primary dysmenorrhea is a common issue experienced by adolescents and disrupts daily activities. The use of analgesic medications is a common method to reduce the perceived pain; however, some patients do not recover and continue to experience discomfort. Alternative interventions, such as acupuncture, can reduce uterine inflammation and ischemia, thereby alleviating pain. The purpose of this study is to determine the effectiveness of acupuncture therapy and auricular acupuncture for primary dysmenorrhea in the service area of Puskesmas 1, Denpasar Timur Health Office, from June to August 2024. This study employs a quasi-experimental, non-equivalent control group pre-test post-test design, using two treatment groups: one group receiving acupuncture therapy and the other auricular acupuncture therapy. A total of 36 participants were recruited using purposive sampling and underwent 12 therapy sessions. Data analysis was conducted using the Shapiro-Wilk test, with a significance value of 0.007, which is less than 0.05, indicating non-normal distribution. Consequently, the Mann-Whitney U test was used to determine the difference in means. Statistical analysis showed a calculated Z value of -4.233 with a significance level of 0.000, which is lower than the probability threshold, indicating a statistically significant difference between the two groups. The acupuncture group exhibited greater pain reduction compared to the auricular acupuncture group.